2007
DOI: 10.1007/bf02977333
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting analysis of fresh ginseng roots of different ages using1H-NMR spectroscopy and principal components analysis

Abstract: Fingerprinting analysis of fresh ginseng according to root age was performed using 1H-NMR spectroscopy and multivariate analysis techniques. Various peaks were detected in the aliphatic (0-3 ppm), sugar (3-6 ppm), and aromatic (6-9 ppm) regions of the 1H-NMR spectra of the water extracts of fresh ginseng root. The use of principal components (PCs) analysis (PCA) for metabolomic profiling allowed the large 1H-NMR data set obtained for various metabolites to be reduced to PC1, PC2, and PC3. Two dimensional score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…Calcium oxalate and fatty acids in ginseng root also can vary depending on the cultivation area or method [33]. It has been also shown that quantitative changes in aromatic compounds can be used to discriminate ginseng roots with different ages [28]. In the case of the olive tree, secondary metabolites in leaves play a significant role in cultivar discrimination by multivariate analysis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium oxalate and fatty acids in ginseng root also can vary depending on the cultivation area or method [33]. It has been also shown that quantitative changes in aromatic compounds can be used to discriminate ginseng roots with different ages [28]. In the case of the olive tree, secondary metabolites in leaves play a significant role in cultivar discrimination by multivariate analysis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Abundant fragment ions by multi-stage MS and high mass accuracy by TOF-MS offer structural information and the possibility of identifying unknown components. In NMR-based fingerprinting, the 1 H NMR spectrum provides a wealth of chemical information on ginseng 212, 238. NMR has the highest reliability in metabolomics 118.…”
Section: Applications and Challengesmentioning
confidence: 99%
“…Several studies have used NMR-based methods on plant material, demonstrating biochemical differences according to tissue age, geographical location, genetic modification, and response to stress. For example, Shin et al (2007) performed fingerprinting analyses of fresh, differently old ginseng roots using 1 H-NMR spectroscopy and multivariate analysis techniques. The authors detected various distinct peaks in the 1 H-NMR spectra of the liquid-state ginseng roots.…”
Section: Suitability Of Other Spectroscopic Techniques For Root Analysesmentioning
confidence: 99%